Evaluation of the level of some Interleukins in serum of Iraqi patients with Endometrial Carcinoma - Hameed, Hajer S.; Yenzeel, Jabbar H.; Sabbah, Majeed A. (Iraqi Journal of Science, 2023)
Endometrial Cancer (EC) is one of the most common malignancy of the female reproductive system. With an increasing incidence, it is important to improve the new prognosis ways for its pre-diagnosis that must be early, accurate and effective. This study aimed to search for biological (like some new interleukins) which could help in early diagnosis of EC before the hysterectomy. Currently not enough research is being done exploiting linking between the interleukins submitted in this study and EC. Epically IL-36 and IL-38, which have been recently described and are still under study in the world. This study is the first of its kind in Iraq. Fifty-five patients with EC (mainly in their first or second stage, due to early diagnosis and who newly have the symptoms and pain as a result of cancer) and 57 healthy controls (with ages up to 45) were involved in this study. To measure the concentration of the following interleukins: IL-27, 31, 33, 35, 36 and 38 by ELISA, blood samples were collected from women via vein puncture. The results of this study showed a highly significant (P≤0.01) increase in Interleukin 27 (IL-27), Interleukin 31 (IL-31) and Interleukin 33 (IL-33) among all studied interleukins levels in EC patient as compared with healthy controls. Interleukin 35 (IL-35), Interleukin 36 (IL-36) and Interleukin 38 (IL-38) also showed highly significant (P≤0.01) increase in EC patients as compared with healthy women. The significant increase (P≤0.01) of these interleukins can be used to help in the early diagnosis and treatment of EC, without need to hysterectomy or histological diagnosis.